Heat and Mass Transfer Predictive 3D Model of Mango Kernel During Convection Oven Drying Process - Islam, Md Shafiul; Ali, Md Sumon; Rahman, Mohammad Nurur; Das, Pabitra Chandra (Chemical Engineering Research Bulletin, 2021)
A large number of mangoes are utilized in process industries which produce a large amount of mango kernel that can be utilized effectively as a by-product. Processing and utilization of mango kernel flour is getting more scientific interest day by day. Drying is one of the major operations of flour processing where the moisture loss and heat transfer phenomena across the different portions of the products have to be pre-defined for better drying accuracy. The study was conducted to define a compatible predictive model that represents a 3D expression of heat penetration through the mango kernel slice (MKS) and moisture losses during drying with convective oven dryer using COMSOL Multiphysics with originated boundary conditions, excluding the changes of properties due to varying mangoes species. The model was validated using a convective drying process for varying thicknesses 4, 6 and 8 mm of MKSs having temperature elevated to 60oC and 1 ms-1 air velocity up to 5 hr. The developed model was concurred and correlated well with the experimental data and can be used in describing heat and mass transfer phenomena while drying the mango kernel. Chemical Engineering Research Bulletin 21(2020) 82-87